2022
DOI: 10.3171/2021.7.peds20836
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic disparities in fetal surgery for myelomeningocele: a single-center retrospective review

Abstract: OBJECTIVE Fetal surgery for myelomeningocele has become an established treatment that offers less risk of requiring a ventricular shunt and improved functional outcomes for patients. An increasing body of literature has suggested that social determinants of health have a profound influence on health outcomes. The authors sought to determine the socioeconomic and racial and ethnic backgrounds of patients who were treated with fetal surgery versus those who underwent postnatal repair. METHODS Demographic data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This observation suggests that other confounding variables may be at play, such as insurance status limiting access to follow‐up ultrasounds, differences in the quality and interpretation of the ultrasound itself, or availability of referrals and/or transportation to a tertiary medical center for prenatal consultation. Our findings are consistent with prior studies that have shown differences in obstetric care and neonatal outcomes between those with government issued insurance and those with commercial insurance 19–21 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation suggests that other confounding variables may be at play, such as insurance status limiting access to follow‐up ultrasounds, differences in the quality and interpretation of the ultrasound itself, or availability of referrals and/or transportation to a tertiary medical center for prenatal consultation. Our findings are consistent with prior studies that have shown differences in obstetric care and neonatal outcomes between those with government issued insurance and those with commercial insurance 19–21 …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with prior studies that have shown differences in obstetric care and neonatal outcomes between those with government issued insurance and those with commercial insurance. [19][20][21] Our study, while one of the first of its kind to be reported, has significant limitations. Most notable is our lack of objective measurements of micrognathia and retrognathia (inferior facial angle or jaw index) for most patients.…”
Section: Discussionmentioning
confidence: 93%
“…Significant disparities exist. Patients with low socioeconomic status, those who lack private insurance and those who are people of colour are less likely to undergo foetal spina bifida closure (Foy et al, 2021; Wilpers et al, 2022).…”
Section: Addressing Spina Bifidamentioning
confidence: 99%
“…Even those with access to health care encounter additional impediments to specific services. Patients of colour are twice as likely to suffer from multiple maternal comorbidities and pregnancy complications that may disqualify them from eligibility for closure (Foy et al, 2021). In my practice, maternal obesity (i.e., body mass index >40) is the most common comorbidity to impact eligibility for foetal closure, followed by high blood pressure, gestational diabetes and sexually transmitted infections.…”
Section: Barriers To Access and Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation